2020
DOI: 10.1016/j.snb.2020.128143
|View full text |Cite
|
Sign up to set email alerts
|

Acoustofluidic closed-loop control of microparticles and cells using standing surface acoustic waves

Abstract: Precise, automatic and reliable position control of micro-objects such as single particles, biological cells or bio-organisms is critical for applications in biotechnology and tissue engineering. However, conventional acoustofluidic techniques generally lack reliability and automation capability thus are often incapable of building an efficient and automated system where the biological cells need to be precisely manipulated in three dimensions (3D). To overcome these limitations, we developed an acoustofluidic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 72 publications
0
28
0
Order By: Relevance
“…When cells are in abnormal states-including cells that have undergone malignant transformation, damage, or apoptosis-related changes-their secreted exosomes contain altered protein and molecular signatures 10 . Circulating exosomes found in the blood have been studied as potential targets for the development of blood-based point-of-care diagnostic platforms for cancer 11,12 . Because exosomes are released into circulation, they offer the potential to detect remote lesions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When cells are in abnormal states-including cells that have undergone malignant transformation, damage, or apoptosis-related changes-their secreted exosomes contain altered protein and molecular signatures 10 . Circulating exosomes found in the blood have been studied as potential targets for the development of blood-based point-of-care diagnostic platforms for cancer 11,12 . Because exosomes are released into circulation, they offer the potential to detect remote lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we demonstrate an acoustofluidic (a combination of acoustics and microfluidics) 23,24 device as a potential solution for exosome-based TBI diagnosis [25][26][27][28] . The underlying mechanism of acoustofluidics uses acoustic waves to generate acoustic radiation forces on particles in the fluid; the strength of the acoustic radiation force depends on the size and density of the particle 12,[29][30][31][32][33] . The high biocompatibility of acoustofluidic devices also benefits downstream analysis by providing samples with complete structures and components [34][35][36][37][38] .…”
Section: Introductionmentioning
confidence: 99%
“…[ 35,36 ] In addition, we have previously shown that SAW devices are capable of patterning polymer microparticles into 3D matrix structures, [ 15,37 ] as well as precisely and reliably controlling the 3D position of single microparticles and cells. [ 38 ] However, to date, no studies have explored the use of the reusable SAW or acoustofluidic device for rapid 3D patterning of biological objects in scaffold‐based hydrogels contained in a millimeter‐scale microfluidic chamber.…”
Section: Introductionmentioning
confidence: 99%
“…Acoustofluidics, which integrates acoustic waves with microfluidics to manipulate particles and fluids in microscale fluid, has been widely used in material engineering [ 1 , 2 , 3 ] and biotechnology [ 4 , 5 ], due to the advantages of noncontact, better biocompatibility, and compactness [ 6 ]. Surface acoustic waves (SAWs), which are generated and propagated on the surface, have attracted attention for the following reasons.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers found that the SSAWs’ thermal effect is key in the application of acoustofluidics because of the destruction of bio-particles [ 28 ]. To overcome the high temperature in acoustofluidics, cooling equipment had to be integrated into microfluidics [ 6 , 29 ]. However, few have measured the temperature induced by the SSAWs’ thermal effect in the microchannel, which limited the precise controlling and application of particles in the biological detection of SSAW-based devices.…”
Section: Introductionmentioning
confidence: 99%